Adhesives from liquefied eucalypt bark and branches - Esteves, Bruno (2019)
Adhesives made from lignin are one of the most promising alternatives to common ureaformaldehyde adhesives. One of the possible sources is from wood or bark liquefaction at low temperatures and pressure. The possibility of using forest wastes for the production of adhesives was the objective of this work. Eucalypt bark and branches are wastes produced in the company Pedrosa & Irmãos, which is a forest management company based in Portugal (Leiria). The wastes were liquefied with polyalcohols catalyzed by sulfuric acid. The water insoluble fraction of the liquefied material was used for the production of the bio-adhesive. Both fractions were characterized and the bonding performance of the bio-adhesive was tested by ABES. The bio-adhesives obtained from bark or branches were similar, exhibiting a bonding strength approximately half of the conventional UF resin.